О принципах определения вводных и вставных конструкций - Гедминайте, Ирена (Kalbotyra, 1985)
The article is devoted to the problem of distinction between parenthetical and inserted clauses in English. The distinction between the two was originally elaborated in Russian linguistics, where it is described in semantic and phonetic terms. In this article the possibility of theme and rheme analysis of parenthetical and inserted clauses is presented.